Digital Libraries: Achievements, Challenges and Opportunities 9th International Conference on Asian Digial Libraries, ICADL 2006, Kyoto, Japan, November 27-30, 2006, Proceedings - Sugimoto, Shigeo; Hunter, Jane; Rauber, Andreas; Morishima, Atsuyuki (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2006)
The International Conference on Asian Digital Libraries (ICADL) was born in Hong Kongin 1998and hosted in Taipei (1999),Seoul(2000),Bangalore(2001), Singapore (2002), Kuala Lumpur (2003), Shanghai (2004) and Bangkok (2005). ICADL 2006 held in Kyoto, Japan was the 9th of the ICADL series. ICADL has been recognized as an important event for the digital library communities not only in Asia but also globally. The primary mission of ICADL, like the Joint Conference on Digital Libraries (JCDL) and European Conference on Digital Libraries (ECDL), is to serve as a forum for exchange of new advanced te- nologies and ideas among researchers and practitioners. In addition, ICADL as a conference based in Asia is an important event not only for people in dev- oped countries but also in developing countries where there is large diversity in culture, language and development. ICADL 2006received170papersubmissionsfrom23countries.Everysubm- sion was reviewed by at least three reviewers. The Program Committee selected 46 full papers and 14 short papers based on the quality and contribution to digital library research. ICADL as well as JCDL and ECDL cover a wide range of information technologies for digital libraries as well as the human and social aspects of digital libraries. The topics of the papers in the proceedings include information extraction, information retrieval, metadata, architectures for di- tal libraries and archives, ontologies, information seeking, cultural heritage and e-learning.